A COMPARISON OF INTRAPERITONEAL INSTILLATION OF ROPIVACAINE AND ROPIVACAINE WITH DEXMEDETOMIDINE FOR POSTOPERATIVE ANALGESIA FOLLOWING LAPAROSCOPIC CHOLECYSTECTOMY: A PROSPECTIVE STUDY - SHARMA, PRIYANKA; SAINI, PRIYANKA; SHARMA, MEGHA; KHANDELWAL, MANISH (International Journal of Current Pharmaceutical Research, 2024)
Objective: laparoscopic cholecystectomy surgeries are having advantages over open cholecystectomy with less pain and quick recovery. Intraperitoneal route of administration of a local anaesthetic is a cheap, easy and non-invasive method of reducing the intensity of post laparoscopic pain. This study compared the postoperative analgesic effect of intraperitoneal instillation of ropivacaine 0.5% and ropivacaine 0.5% with dexmedetomidine (1µg/kg) in patients undergoing laparoscopic cholecystectomy under general anaesthesia. Methods: Total 86 patients were divided equally in 2 groups. Patients in group R received 20 ml 0.5% isobaric ropivacaine hydrochloride+5 ml NS where in Group RD, patients received 20 ml 0.5% isobaric ropivacaine hydrochloride with 1µg/kg dexmedetomidine hydrochloride. Solution was diluted with normal saline to make a total volume 25 ml. Hemodynamic parameters were noted during surgery Postoperatively, patient was assessed for pain using the visual analogue scale (VAS) at 30 min, then 2,4,8,12 and 24 h. Total analgesic consumption in the first 24 h also compared. Results: Baseline demographic profile of study participants were similar. Mean duration of analgesia was significantly higher in group RD (10.05±6.916 h) as compared to group R (5.59±6.8) (p=0.003). Mean dose of rescue analgesia was significantly higher in group R (130.81±61.44) as compared to group RD (75±36.6) (p<0.001). VAS score was significantly higher in group R as compared to group RD at different time intervals. Conclusion: We concluded that intraperitoneal Ropivacaine with Dexmedetomidine produced postoperative analgesia better than ropivacaine alone.